Adherence Rate, Barriers to Attend, Safety, and Overall Experience of a Remote Physical Exercise Program During the COVID-19 Pandemic for Individuals After Stroke - Torriani-Pasin, Camila; Palma, Gisele Carla dos Santos; Makhoul, Marina Portugal; Antonio, Beatriz de Araujo; Lara, Audrea R. Ferro; Silva, Thaina Alves da; Caldeira, Marcelo Figueiredo; Júnior, Ricardo Pereira Alcantaro; Domingues, Vitoria Leite; Freitas, Tatiana Beline de; Mochizuki, Luis (Frontiers in Psychology, 2021)
Introduction: The actions taken by the government to deal with the consequences of the coronavirus diseases 2019 (COVID-19) pandemic caused different levels of restriction on the mobility of the population. The need to continue offering physical exercise to individuals after stroke became an emergency. However, these individuals may have barriers to adhere to the programs delivered remotely. There is a lack of evidence related to adherence, attendance, safety, and satisfaction of remote exercise programs for this population. Objective: The aim was to evaluate adherence and barriers to attend a remote physical exercise program for individuals after stroke. We aimed (a) to identify adherence and attendance rate of the remote physical exercise program (i.e., number of participants engaged, number of sessions attended, and exercise time in remote program); (b) to identify the safety of a remote physical exercise program (i.e., falls, pain, or dizziness when performing the exercises, fear, or insecurity); and (c) to identify the overall experience to participate in a remote program. Materials and methods: This is a longitudinal study, including 36 stroke survivors who already attended a face-to-face physical exercise program prior to the COVID-19 pandemic. The remote physical exercise program included sessions for 2 days/week for a duration of 22 weeks, with a total of 44 sessions, which were delivered asynchrony via recorded video sessions. As outcome measures, we performed two questionnaires (via weekly telephone calls) to identify attendance, barriers, safety, and overall experience related to the program. Results: The adherence rate was 86 (9%). The attendance rate was 19, with a total of 8 sessions (108.3 min/week). The main barriers for lower attendance rate were as follows: lack of motor skills and physical fitness to workout in 80 reports (20.6%), followed by no exercise companion in 44 reports (11.3%). The remote physical program has been shown to be safe, and the overall experience was positive from the perspectives of the participants and the family members. Conclusion: Although the adherence rate was high, the attendance rate was low on the remote physical exercise program. The main barriers to attending the program remotely reflect the need of tailoring individually an asynchrony mode of delivering the sessions to individuals after stroke. Our results also indicate how the COVID-19 impacted the health conditions of stroke survivors. The program was safe, and the overall experience indicated a change in the mental, physical, and social health of individuals after stroke and their family members.